Reasoning Web. Reasoning and the Web in the Big Data Era 10th International Summer School 2014, Athens, Greece, September 8-13, 2014. Proceedings - Koubarakis, Manolis; Stamou, Giorgos; Stoilos, Giorgos; Horrocks, Ian; Kolaitis, Phokion; Lausen, Georg; Weikum, Gerhard (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2014)
This volume contains the lecture notes of the 10th Reasoning Web Summer School 2014, held in Athens, Greece, in September 2014. In 2014, the lecture program of the Reasoning Web introduces students to recent advances in big data aspects of semantic web and linked data, and the fundamentals of reasoning techniques that can be used to tackle big data applications.